Model Pendidikan Karakter Peduli Lingkungan Berbasis Agama dan Budaya Lokal: Studi Kasus di Masyarakat Adat Kampung Dukuh Kecamatan Cikelet Kabupaten Garut - Ida Rosyida (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to form a model of character education that cares about the environment in religious-based forest conservation which has characteristics in accordance with the realities of life and culture of the indigenous people of Kampung Dukuh, Ciroyom Village, Cikelet District, Garut Regency in particular and rural communities in general. The method used is a qualitative approach, namely research that does not carry out calculations (numbers) in carrying out epistemological justification. As a result, the indigenous people of Kampung Dukuh live their social life based on religious and cultural values ​​that refer to the sayings of their ancestors.